Study of Dissolved Iron in Some ground Water Samples of Rajnandgaon Region of Madhya Pradesh Using N-Hydroxyamidine and Thiocyanate - Tiwari, Sushil; Khan, Shabaz; Hemlata Mohabey, (Miss) (Asian Journal of Chemistry, 2010)
Ground water delivered by some bore wells of Rajnandgaon area are slightly turbid, having slow sedimentation causing reddish precipitate. Ten such spots were selected for the collection of ground water samples through borewells. These water samples have been characterised in terms of pH, total dissolved solid, total hardnesss and iron concentration. A new method has been developed for determination of iron(III) using N-hydroxy-N-o-chlorophenyl-N'-(3- methyl) phenyl p-toluimidine hydrochloride in presence of thiocyanate. The orange-red complex is easily extractable in benzene and suitable for spectrophotometric determination. The coloured system obeys Beer's law in the range. 0.4-0.4 ppm. The ternary complex shows maximum absorbance at 460 nm having its molar absorptivity to be 12000 ± 50 1 mole-1. The method is free from interference of many common ions. The pH values of the selected samples are within permissible limit (6.8-8.3). TDS is in the range 130-900 ppm and total hardness 330-1130 ppm. The iron content was found to be in the range 0.1-3.0 ppm.